Child Mortality in Rural India - Van der Klaauw, Bas; Wang, Limin (World Bank, Washington, DC, 2013)
The authors focus on infant and child mortality in rural areas of India. They construct a flexible duration model framework that allows for frailty at multiple levels and interactions between the child's age and individual socioeconomic, and environmental characteristics. The model is estimated using the 1998-99 wave of the Indian National Family and Health Survey. The estimated results show that socioeconomic and environmental characteristics have significantly different effects on mortality rates at different ages. These are particularly important immediately after birth. The authors use the estimated model for policy experiments. These indicate that child mortality can be reduced substantially, particularly by improving the education of women and reducing indoor air pollution caused by cooking fuels. In addition, providing access to electricity and sanitation facilities can reduce under-five-years mortality rates significantly.